Swallows, Freedom and Valparaíso. The Use of Urban Land and the Emergence of Borders as Generators of Identity in Residential Areas - Letelier Parga, Sofía (Revista INVI, 1994)
The anthropological capacity to give a proper use to soils in the urban settlements -which each society would express in normal results of identify- is lacking in the Chilean context. It is believed that since the profesionalization of architecture, architects acting as t4eh only interpreters of collective as well as individual space - formal expectatives have not been able to supply such anthropological capacity. The latter has actually been deepened due to the fact that the architect's formation lacks the necessary tools for such interpretation and they even create a normative tool which is negative as regards the generation of identify. all this would affect the social residential areas where the architect's work is meant for anonymous groups with would coincide with the anonymity, the urgency, the massiveness and the severe resource scarcity, all of which is accompanied by the architect's remoteness. A change started by the architects is needed so as to after this situation.